Older women are frailer, but less often die than men: a prospective study of older hospitalized people. (October 2019) - Veronese, Nicola; Siri, Giacomo; Cella, Alberto; Daragjati, Julia; Cruz-Jentoft, Alfonso J.; Polidori, Maria Cristina; Mattace-Raso, Francesco; Paccalin, Marc; Topinkova, Eva; Greco, Antonio; Mangoni, Arduino A.; Maggi, Stefania; et al.
Highlights: Hospitalized older women were frailer than hospitalized older men, but experienced a lower in-hospital and one-year death rate. The women were admitted more frequently to a nursing home in the year after hospital discharge. The women experienced a lower rate of rehospitalization than the men. Hospitalized older women were frailer than hospitalized older men. Women experienced a lower in-hospital and one-year death rate. Abstract: Objectives: The association between frailty, mortality and sex is complex, but a limited literature is available on this topic, particularly for older hospitalized patients. Therefore, the objective of our study was to prospectively evaluate sex differences in frailty, assessed by the Multidimensional Prognostic Index (MPI) and mortality, institutionalization, and re-hospitalization in an international cohort of older people admitted to hospital. Study design: We used data from nine public hospitals in Europe and Australia, to evaluate sex differences in mortality, frailty and the risk of institutionalization and re-hospitalization, during one year of follow-up. Main outcome measures: People aged 65 years or more admitted to hospital for an acute medical condition or for a relapse of a chronic disease were included. A standardized comprehensive geriatric assessment, which evaluated functional, nutritional, and cognitive status, risk of pressure sores, comorbidities, medications and co-habitation status, was used to calculate the MPI to measure frailty in all hospitalized older people. Data regarding mortality, institutionalization and re-hospitalization were also recorded for one year. Results: Altogether, 1140 hospitalized patients (mean age = 84.2 years; 694 women = 60.9%) were included. The one-year mortality rate was 33.2%. In multivariate analysis, adjusted for age, MPI score, centre and diagnosis at baseline, although women had higher MPI scores than men, the latter had higher in-hospital (odds ratio, OR = 2.26; 95% confidence intervals, CI = 1.27–4.01) and one-year post-discharge mortality (OR = 2.04; 95%CI = 1.50–2.79). Furthermore, men were less frequently institutionalized in a care home than female patients (OR = 0.55; 95%CI: 0.34–0.91), but they were also more frequently re-hospitalized (OR = 1.42; 95%CI: 1.06–1.91) during the year after hospital discharge. Conclusion: Older hospitalized men were less frail, but experienced higher in-hospital and one-year mortality than women. Women were admitted more frequently to nursing homes and experienced a lower risk of re-hospitalization. These findings suggest important differences between the sexes and extends the 'male-female health-survival paradox' to acutely ill patient groups.